Pengaruh Corporate Governance Terhadap Agency Cost Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Alya Nisrina Hafsyah; Mega Mersela; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to determine the effect of corporate governance on agency costs. The sample used for this research is manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2020 period, which total 66 companies. The technique for taking samples in this research is purposive sampling and panel data regression analysis methods. The independent variables used are board size, board independence, management ownership and foreign ownership and the control variables are leverage, firm size, firm performance with agency cost as the dependent variable.